Optimum methods of underground ore mining in Siberia - Jurij V. Mihaylov (Mining science and technology, 2018)
The problem of underground ore mining in Siberian lies in developing deposits in permafrost conditions – cryolithic zone, which covers 64% of the territory of Russia. The difficulty of completeness of mineral extraction with ensuring environmental safety in the permafrost zone lies primarily in the extremely high sensitivity of this zone to any technogenic impact. Mining industry has a great impact on the entire biosphere: atmosphere, lithosphere, hydrosphere, and, first of all, causes air pollution. To manage air pollution during subsoil use, improving mining methods and techniques, decreasing emission of toxic gases, dust and capturing them in mined-out space to prevent their release into the atmosphere is required. The question of national security of Russia is selective mining of only rich ore areas, which leads to premature closure of mining enterprises and losses of strategic raw materials. The situation can be corrected by applying methods to avoid large losses of valuable ores in the subsoil. In this paper, the methods are considered that ensure high-performance mining, environmental safety and national security in the conditions of permafrost zone of Siberia.